Open government data in health sector: a systematic literature review - Patrícia Nascimento Silva; Sarah Nascimento Silva (BMC Public Health)
Abstract Background Open government data (OGD) in the health sector consolidates transparency, access to information, and collaboration between the government and different sectors of society. It is an essential instrument for health systems and researchers to generate initiatives, drive innovations, and qualify decision-making, whether in health emergencies or supporting the creation of more effective public policies. This review aimed to identify OGD initiatives in healthcare and their possible applications. Methods A systematic search was conducted in the MEDLINE (PubMed), Web of Science, Scopus, and Scielo databases up to February 12, 2024. Eligibility criteria included original studies that addressed OGD initiatives in public health. Studies using open data to prepare other analyses, reviews, and opinion articles were excluded. The quality methodological of related studies was based on the JBI Critical Appraisal tool. Data extraction included the location of the application, description of the initiative/use of data, themes addressed, data quality, and respective evaluation tools. Results Of the 3,176 records initially identified, six studies were included describing initiatives to make available datasets or portals that publish OGD in the healthcare area between 2020 and 2023. Most publications evaluated quality and usability requirements, with five related to the COVID-19 pandemics. There is significant heterogeneity in the data formats available, obtaining, on average, a 3-star rating in the Berners-Lee evaluation model. The availability of open data presents geographic differences, with regions being more developed than others in both the most comprehensive and the most regionalized studies. Conclusions Few studies using OGD in health were identified in the scientific literature. The heterogeneity of open data formats, the lack of standards, and the quality of the data point to limitations and the need for improvements to enable the use and reliable reuse of this data. Trial registration PROSPERO CRD42024498446.